Inequality and housing: a consubstantial analysis of social relations of sex/gender, class, and race (Temporalis, 2026)
Social rights, including the right to housing, are indispensable rights for human beings. Despite this, there are challenges in effectively implementing this right in a dignified manner. This reality is linked to the actions of the capitalist state, which organizes cities into distinct spaces for certain groups in society. In this scenario, socio-spatial inequality, anchored in social relations of sex/gender, class, and race, becomes the basis that renders a certain population invisible, forcing them to survive in precarious conditions in the territories they inhabit, thus flourishing socio-spatial inequality. Considering the contributions of feminist studies in the context of inequality in capitalist society, this article aims to critically analyze socio-spatial inequalities and the right to housing from the perspective of consubstantiality, as it allows us to understand the complexity of this phenomenon through the interweaving of social relations of sex/gender, class, and race. The research sources were based on a qualitative bibliographic survey. Based on our analysis, we conclude that social relations of sex/gender, class, and race perpetuate lack of access to housing and housing inequalities, violating the right to the city and to citizenship itself. Considering that, at the heart of capitalism, socio-spatial inequalities are fundamental to its reproduction. Given this, it is necessary to reconstruct this scenario, using the analysis made by consubstantiality, which, by understanding the interweaving of social relations of sex/gender, class, and race, contributes to the construction of consubstantialized public housing policies as a condition for reducing manifestations of inequality.
Keywords: Consubstantiality; Housing; Socio-spatial inequalities; Social relations